Changes in mechanical work during neural adaptation to asymmetric locomotion - Selgrade, B. P.; Thajchayapong, M.; Lee, G. E.; Toney, M. E.; Chang, Y.-H. (The Journal of Experimental Biology, 2017)
Minimizing whole-body metabolic cost has been suggested to drive the neural processes of locomotor adaptation. Mechanical work performed by the legs should dictate the major changes in whole-body metabolic cost of walking while providing greater insight into temporal and spatial mechanisms of adaptation. We hypothesized that changes in mechanical work by the legs during an asymmetric split-belt walking adaptation task could explain previously observed changes in whole-body metabolic cost. We predicted that subjects would immediately increase mechanical work performed by the legs when first exposed to split-belt walking, followed by a gradual decrease throughout adaptation. Fourteen subjects walked on a dual-belt instrumented treadmill. Baseline trials were followed by a 10-min split-belt adaptation condition with one belt running three times faster than the other. A post-adaptation trial with both belts moving at 0.5 m s-1 demonstrated neural adaptation. As predicted, summed mechanical work from both legs initially increased abruptly and gradually decreased over the adaptation period. The initial increase in work was primarily due to increased positive work by the leg on the fast belt during the pendular phase of the gait cycle. Neural adaptation in asymmetric split-belt walking reflected the reduction of pendular phase work in favor of more economical step-to-step transition work. This may represent a generalizable framework for how humans initially and chronically learn new walking patterns